MODELING DIGITAL ADOPTION IN THE HALAL SECTOR: A UTAUT-BASED QUANTITATIVE STUDY OF MSMES IN EAST KALIMANTAN - Tikawati; Siti Qomariah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Objective: This study aims to examine the factors influencing the adoption of digital marketing among halal MSMEs in East Kalimantan using the UTAUT framework, by testing hypotheses H1–H8: the effects of performance expectancy (PE), effort expectancy (EE), and social influence (SI) on behavioral intention (BI); the effect of personal innovativeness (PI) on BI; the effect of BI on use behavior (UB); and the moderating role of PI on the relationships between PE→BI, EE→BI, and SI→BI. Methods: This study employed a quantitative survey approach using primary data collected through questionnaires from 100 halal MSME actors in East Kalimantan, selected using non-probability purposive sampling with the following criteria: marketing halal products, domiciled in East Kalimantan, and having used at least one digital marketing channel. Respondents were predominantly female (84%), aged 31–50 years, and business owners (87%). The latent variables measured included PE (2 indicators), EE (3), SI (2), PI (2), BI (3), and UB (1). Data were analyzed using PLS-SEM with bootstrapping procedures and one-tailed significance testing (α = 0.05). Results: The findings indicate that the intention to use digital marketing among halal MSMEs is more strongly shaped by social influence and individual innovativeness than by perceived performance benefits or perceived ease of use. The formed intention is consistently associated with actual digital marketing usage behavior. In addition, personal innovativeness was found to moderate the effects of perceived usefulness and perceived ease of use on intention, but did not moderate the influence of social factors on intention. This pattern suggests that digital marketing adoption decisions among halal MSMEs in the study area are primarily driven by social dynamics and the innovative disposition of business owners, while usefulness and ease of use are not always direct determinants when business actors already have initial exposure to digital channels. Implications: The findings emphasize the importance of strengthening social ecosystems (communities, networks, and customer encouragement) and enhancing the personal innovativeness of business owners to reinforce intention and promote actual use of digital marketing among halal MSMEs. Practical recommendations include community-based mentoring, digital literacy programs emphasizing guided experimentation, and training in performance measurement. Future studies are encouraged to expand sample size and diversity, enrich the measurement of use behavior with multi-item or behavioral indicators, and incorporate implementation determinants (e.g., facility support and digital capabilities) to improve explanatory power.